An appraisal of the legal framework for combating drug trafficking in Nigeria - Agbonika, John A. M. (African journal of law and criminology, 2015)
This article examines the legal response of the Government of Nigeria to the problem of drug trafficking. Incidentally, Nigerians have stood out as very active drug traffickers. Underdevelopment and poverty present in producer countries, which are also evident in Nigeria, are partly to blame. Economic difficulties notwithstanding, Nigeria has joined the global community in enacting legislation outlawing such acts as trafficking and possession of drugs. The ultimate objective of this Article is to appraise the legal framework for combating Drug trafficking in Nigeria, scope of Drug trafficking, Drug trafficking and factors Responsible for it, Defectiveness of the Act visa-vis perceived challenges of the Nigeria Drug Law enforcement agency in fight against trafficking. While supporting the conclusion that the law enforcement has not been effective, one is unable to recommend decriminalization. Rather, suggestions are made with a view to improving law enforcement and international co-operation. Alternative solutions, such as the legal approach, which can go hand-in-hand with law enforcement, are proffered.